Le travail de Rithy Panh : un appareil funéraire - Martine Lefeuvre-Déotte (Appareil)
The Cambodian director and writer, Rithy Panh, born in 1962 in Phnom Penh, is a survivor of the genocide perpetraded by the Pol Pot regime (1975-1979). The Khmer Rouge organized a mass crime (20 % of the population were exterminated). The target, they said, were the enemies of the revolution: the non-Khmers, the intellectuals, the owners, the city people, the middle-class. Their aim was not only to eliminate them but to make them disappear - kamtech in Khmer means not only to kill but to erase all traces, to reduce to ashes, so as to leave nothing of life or death. This crime itself long disappeared; in 1993, the Khmers Rouges were still acknowledged by the UN. How can a society survive to this monstrous oblivion, to this denial, without sinking into madness? The literary and film work of Panh not only endeavours to restore, 20 years along, the truth, methodically, implacably, to flight lies, to bring life to those who have no trace, no story, so as to allow them to a decent grave. By setting them in a narrative and in pictures, Panh allows, in his own way, a mourning ritual for all those who, alike the Mothers of the May Square in Argentina, had tremendously been deprived of it.